(untitled) (Comunicação & Inovação, 2021)
The article analyzes the themes and language worked on in the genre editorial In Her Words, of The New York Times, to understand if there is construction of journalistic texts with gender perspective. The content analysis method allowed the production of journalism from a gender perspective to be observed in the communication vehicle in the In Her Words genre editorial.